TEKNOLOGI MARKETPLACE SEBAGAI UPAYA PENINGKATAN PEMASARAN PRODUK HASIL USAHA KECIL (Infotekmesin, 2018)
Small and medium businesses are very rapidly growing in Indonesia. One of the activities in the small and medium business is the marketing process. The entrepreneurs tend to focus on production activities but for marketing strategies are not developed so that the market share is still local market. The problems that occur in marketing small and medium business products are little knowledge about marketing strategies, marketing targets and willingness to develop from the entrepreneurs themselves.Marketplace systems are built to increase market expansion so that it can help entrepreneurs to do marketing. The marketplace system is built based on the web, both entrepreneurs and buyers can communicate through the web marketplace. The results of this study are that the system can reach broader marketing with small and medium business marketplaces and more targeted.